1990
DOI: 10.1213/00000539-199009000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Cognitive Recovery After General Anesthesia

Abstract: This study was designed to quantify the rate of mental recovery in elderly and young patients after general anesthesia for intraabdominal surgery (cholecystectomy). Forty patients (25-83 yr) were given four tests assessing neuropsychological function once preoperatively and on five occasions postoperatively. Two of the four neuropsychological tests showed impairment in scores in the elderly patients on the first postoperative day (Symbol Digit Modalities Test, P less than 0.004; The Trail Making Test, P less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 19 publications
0
11
0
4
Order By: Relevance
“…The patient is able to communicate with the Health Care Workers (HCWs) during the surgery and the method is safer than general anaesthesia because it is well tolerated, produces less postoperative confusion and delirium than general anaesthesia in the patient [19].…”
Section: Discussionmentioning
confidence: 99%
“…The patient is able to communicate with the Health Care Workers (HCWs) during the surgery and the method is safer than general anaesthesia because it is well tolerated, produces less postoperative confusion and delirium than general anaesthesia in the patient [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has a maximal score of 30 and a score below 23 indicates impaired cognitive function. According to Antony et al 37 , the MMSE has a sensitivity of 87% and a specificity of 82% to detect dementia and delirium. A study using short duration anesthetics concluded that elderly patients presented impaired cognitive function only in the first postoperative day 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A pontuação máxima é 30, e menos de 23 pontos indica cognição prejudicada. De acordo com Antony e col. 37 , o MEEM foi 87% sensível e 82% específico em detectar demência e delírio. Um estudo utilizando anestésicos de curta duração concluiu que pacientes idosos tiveram função cognitiva alterada apenas no primeiro dia pós-operatório 11 .…”
Section: Métodounclassified
“…[3][4][5] Patients thus were advised to avoid driving or other potentially dangerous activities for 24 hr after surgery. The anesthetic drugs and techniques used in these studies are no longer used for ambulatory anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the past, the use of anesthetic agents with prolonged recovery profiles was associated with delayed cognitive failure (24 hr up to several days after anesthesia). [2][3][4][5] However, much of the work demonstrating delayed cognitive impairment after general anesthesia (GA) took place before the advent of short acting anesthetic agents such as sevoflurane, desflurane and propofol. When these agents are used, evidence for the impairment of cognitive function beyond the immediate recovery period is less clear-cut.…”
mentioning
confidence: 99%